High temporal resolution dual-source photon-counting CT for coronary artery disease: initial multicenter clinical experience - Soschynski, Martin; Hagen, Florian; Baumann, Stefan; Hagar, Muhammad Taha; Weiss, Jakob; Krauß, Tobias; Schlett, Christopher L.; Zur Mühlen, Constantin von; Bamberg, Fabian; Nikolaou, Konstantin; Greulich, Simon; Froelich, Matthias F.; et al. (Journal of Clinical Medicine, 2022)
The aim of this paper is to evaluate the diagnostic image quality of spectral dual-source photon-counting detector coronary computed tomography angiography (PCD-CCTA) for coronary artery disease in a multicenter study. The image quality (IQ), assessability, contrast-to-noise ratio (CNR), Agatston score, and radiation exposure were measured. Stenoses were quantified and compared with invasive coronary angiography, if available. A total of 92 subjects (65% male, age 58 ± 14 years) were analyzed. The prevalence of significant coronary artery disease (CAD) (stenosis ≥ 50%) was 17% of all patients, the range of the Agatston score was 0-2965 (interquartile range (IQR) 0-135). The IQ was very good (one, IQR one-two), the CNR was very high (20 ± 10), and 5% of the segments were rated non-diagnostic. The IQ and assessability were higher in proximal coronary segments (p < 0.001). Agatston scores up to 600 did not significantly affect the assessability of the coronary segments (p = 0.3). Heart rate influenced assessability only at a high-pitch mode (p = 0.009). For the invasive coronary angiography (ICA) subgroup (n = nine), the diagnostic performance for CAD per segment was high (sensitivity 92%, specificity 96%), although the limited number of patients who underwent both diagnostic modalities limits the generalization of this finding at this stage. PCD-CCTA provides good image quality for low and moderate levels of coronary calcifications.
Gesehen am 05.09.2023